Synthetic Transmit Aperture in Ultrasound Imaging - TROTS, Ihor; NOWICKI, Andrzej; LEWANDOWSKI, Marcin (Archives of Acoustics, 2009)
The paper describes the use of synthetic transmit aperture (STA) imaging in medical ultrasound. The synthetic aperture (SA) imaging is a novel approach to today's commercial systems. In these systems the image is acquired sequentially one image line at a time that puts a strict limit on the frame rate and the possibility of acquiring a sufficient amount of data for high image quality. This limitation can be lifted by employing SA imaging where the data are acquired simultaneously from all directions over a number of emissions, and the full image can be reconstructed from those data. Due to the complete data set, it is possible to have full transmitting and receiving focusing at the entire image region to improve the contrast dynamic and spatial resolution. The paper describes the STA imaging with a single element transmitting and all elements receiving apertures. In experiments, 32-element linear transducer array with 0.48 mm inter-element spacing and a burst pulse of 100ns duration were used. The single element transmission aperture was used to generate a spherical wave covering the full image region. The 2D ultrasound images of wire phantom are presented to demonstrate the benefits of SA imaging.